Arginine methylation of PPP1CA by CARM1 regulates glucose metabolism and affects osteogenic differentiation and osteoclastic differentiation - Lu Zhang; Guangjun Jiao; Yunhao You; Xiang Li; Jincheng Liu; Zhenqian Sun; Qinghui Li; Zihan Dai; Jinlong Ma; Hongming Zhou; Gang Li; Chunyang Meng; et al. (Clinical and Translational Medicine, 2023)
Abstract Background The imbalance between osteoblasts and osteoclasts may lead to osteoporosis. Osteoblasts and osteoclasts have different energy requirements, with aerobic glycolysis being the prominent metabolic feature of osteoblasts, while osteoclast differentiation and fusion are driven by oxidative phosphorylation. Methods By polymerase chain reaction as well as Western blotting, we assayed coactivator‐associated arginine methyltransferase 1 (CARM1) expression in bone tissue, the mouse precranial osteoblast cell line MC3T3‐E1 and the mouse monocyte macrophage leukaemia cell line RAW264.7, and expression of related genes during osteogenic differentiation and osteoclast differentiation. Using gene overexpression (lentivirus) and loss‐of‐function approach (CRISPR/Cas9‐mediated knockout) in vitro, we examined whether CARM1 regulates osteogenic differentiation and osteoblast differentiation by metabolic regulation. Transcriptomic assays and metabolomic assays were used to find the mechanism of action of CARM1. Furthermore, in vitro methylation assays were applied to clarify the arginine methylation site of PPP1CA by CARM1. Results We discovered that CARM1 reprogrammed glucose metabolism in osteoblasts and osteoclasts from oxidative phosphorylation to aerobic glycolysis, thereby promoting osteogenic differentiation and inhibiting osteoclastic differentiation. In vivo experiments revealed that CARM1 significantly decreased bone loss in osteoporosis model mice. Mechanistically, CARM1 methylated R23 of PPP1CA, affected the dephosphorylation of AKT‐T450 and AMPK‐T172, and increased the activities of phosphofructokinase‐1 and pructose‐2,6‐biphosphatase3, causing an up‐regulation of glycolytic flux. At the same time, as a transcriptional coactivator, CARM1 regulated the expression of pyruvate dehydrogenase kinase 3, which resulted in the inhibition of pyruvate dehydrogenase activity and inhibition of the tricarboxylic acid cycle, leading to a subsequent decrease in the flux of oxidative phosphorylation. Conclusions These findings reveal for the first time the mechanism by which CARM1 affects both osteogenesis and osteoclast differentiation through metabolic regulation, which may represent a new feasible treatment strategy for osteoporosis.